Bio-material human body part (palm fingers) based electronic FET transistor. (1st January 2012) - Kosta, Shiv Prasad; Kosta, Y.P.; Chaudhary, Jitendra Prasad; Vaghela, Piyush R.; Patel, Amit; Patel, Bhavin; Mehta, Harsh; Kosta, Shakti; Bhatele, Mukta; Purnima, S.; Soni, D.
God's inspired study to realise bio-material human body part (hand palm – first and second finger and also single finger) based field effect transistor (FET) configuration with well-conceived architecture is presented in this paper. This brief communication may become the first historical step towards the concept for realisation of human body part based electronic circuit technology (HBECT). The observed technical performance parameters (drain and transfer characteristics) have similarity with technical conventional characteristics (parameter-wise) of semiconductor FET device, the transistor. Impactful obvious applications in medical sciences and technology are spelt-out.